Early destructive lesions in the developing brain: clinical and electrographic correlates Lesões destrutivas precoces no cérebro em desenvolvimento: correlatos clínicos e eletrográficos - Cristiane Low; Eliana Garzon; Henrique Carrete Jr.; Luis Celso Vilanova; Elza Márcia T. Yacubian; Américo C. Sakamoto (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: Early brain insults can cause cavitary lesions including porencephaly (POR) and multicystic encephalopathy (MCE). The objective of this study was to investigate clinical and electrographic correlates associated to these types of destructive brain lesions. METHOD: Patients with POR and MCE were selected and submitted to clinical and Video-EEG monitoring. The following variables were analyzed: demographic data, type of lesion, presence of gliosis, perinatal complications, epilepsy, brain atrophy, and presence and frequency of epileptiform discharges. RESULTS: Twenty patients were included, 65% males, 35% females, ages ranging from 1 to 40 years, 14 with MCE and 6 with POR. Eighteen patients had hemiparesis, 19 had epilepsy (current or in the past), seven of them had refractory seizures, and 16 had epileptiform discharges. All patients with MCE had gliosis while only 2 with POR had it. CONCLUSIONS: No correlation was observed between type of lesion and clinical and electrographical outcome. However, a positive correlation was observed between frequency of discharges and presence of brain atrophy, and between MCE and gliosis. OBJETIVO: Insultos cerebrais precoces podem causar lesões cavitárias incluindo porencefalias (POR) e encefalomalacias multicisticas (EMC). O objetivo deste estudo foi investigar correlatos clínicos e eletrográficos associados a estes dois tipos de lesões destrutivas. MÉTODO: Pacientes com POR e EMC foram selecionados e submetidos à avaliação neurológica e monitorização vídeo-eletrencefalográfica, analisando-se as seguintes variáveis: dados demográficos, tipo de lesão, presença de gliose, complicações perinatais, epilepsia, atrofia cerebral, presença e freqüência de descargas epilépticas. RESULTADO: Vinte pacientes foram incluídos, sendo 65% do sexo masculino, 35% do feminino, idades entre 1 e 40 anos, sendo 14 com EMC e 6 com POR. Dezoito pacientes tinham hemiparesia, 19 tinham ou tiveram epilepsia (7 deles refratários ao tratamento medicamentoso) e 16 deles tinham paroxismos epileptiformes. Todos com MCE tinham gliose associada, contra apenas 2 dos pacientes com POR. CONCLUSÃO: Não houve correlação entre tipo de lesão e evolução clínica e eletrográfica. Houve, entretando, correlação positiva entre freqüência de descargas epilépticas e presença de atrofia cerebral, e entre lesão do tipo EMC e presença de gliose.